1996
DOI: 10.1183/09031936.96.09122565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemithorax irradiation alone or combined with doxorubicin and cyclophosphamide in 47 pleural mesotheliomas: a nonrandomized phase II study

Abstract: E Ef ff fe ec ct t o of f h he em mi it th ho or ra ax x i ir rr ra ad di ia at ti io on n a al lo on ne e o or r c co om mb bi in ne ed d w wi it th h d do ox xo or ru ub bi ic ci in n a an nd d c cy yc cl lo op ph ho os sp ph ha am mi id de e i in n 4 47 7 p pl le eu ur ra al l m me es so ot th he el li io om ma as s: : a a n no on nr ra an nd do om mi iz ze ed Only 3 of the 47 (95% confidence interval (95% CI) -0.6-13%) irradiated tumours responded with a partial response (PR). In 31 patients treated with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 29 publications
0
16
0
7
Order By: Relevance
“…The rates of objective tumour regression have only been between 10 and 30% with cytotoxic monotherapy, having no significant impact on median survival. Combination chemotherapy has shown no clear advantage over single-agent therapy (Linden et al, 1996).…”
Section: Role Of Chemotherapymentioning
confidence: 99%
“…The rates of objective tumour regression have only been between 10 and 30% with cytotoxic monotherapy, having no significant impact on median survival. Combination chemotherapy has shown no clear advantage over single-agent therapy (Linden et al, 1996).…”
Section: Role Of Chemotherapymentioning
confidence: 99%
“…Although radiation therapy has shown efficacy on mesothelioma cell lines [77], it has proven disappointing in mesothelioma patients and poor results have been described in several series [78,79]. One of the major problems in performing radiation therapy is determining the volume of the target area, which includes the diaphragm, mediastinum, and chest wall and excludes the lung.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Median survival was only 4 months. In a second study in Sweden [49], 47 patients received 40 Gy in 20 fractions to the hemithorax; 16 subsequently received doxorubicin and cyclophosphamide. Only 1 of 31 (3%) exhibited a partial response, and the authors reported no favorable effect on chest pain, weight loss, and performance status.…”
Section: Radiotherapy For Palliation Of Symptomsmentioning
confidence: 99%